2022
DOI: 10.3390/ijms23169003
|View full text |Cite
|
Sign up to set email alerts
|

Upconversion Nanostructures Applied in Theranostic Systems

Abstract: Upconversion (UC) nanostructures, which can upconvert near-infrared (NIR) light with low energy to visible or UV light with higher energy, are investigated for theranostic applications. The surface of lanthanide (Ln)-doped UC nanostructures can be modified with different functional groups and bioconjugated with biomolecules for therapeutic systems. On the other hand, organic molecular-based UC nanostructures, by using the triplet-triplet annihilation (TTA) UC mechanism, have high UC quantum yields and do not r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 164 publications
0
5
0
Order By: Relevance
“…However, a recent study reported that autofluorescence affects in vivo imaging even in the NIR II window [ 35 ]. To overcome this problem, upconverting NPs can be used, which are excited by multiple photon interactions to produce a single photon with energy greater than each incoming photon; upconverting NPs are especially convenient since very few organic molecules with upconverting optical properties exist in the living tissues [ 36 , 37 , 38 ].…”
Section: Nanotechnology and Urinary Bladder Imagingmentioning
confidence: 99%
“…However, a recent study reported that autofluorescence affects in vivo imaging even in the NIR II window [ 35 ]. To overcome this problem, upconverting NPs can be used, which are excited by multiple photon interactions to produce a single photon with energy greater than each incoming photon; upconverting NPs are especially convenient since very few organic molecules with upconverting optical properties exist in the living tissues [ 36 , 37 , 38 ].…”
Section: Nanotechnology and Urinary Bladder Imagingmentioning
confidence: 99%
“…For instance, coumarin has a longer activation wavelength due to its larger area of 𝜋 threshold electrons compared to ONB, so it is proposed that extending the threshold electron area of the photoresponse component is a way to redshift the maximum wavelength of light absorption. [80] At present, there are two technologies for achieving near-infrared photochemical reactions, namely two-photon absorption (TPA) [284,285] and up-conversion (UC) [286,287] based on rare earth materials. TPA technology excites photosensitive components by exposing them to high intensity focused lasers, causing them to instantly absorb a pair of photons with half the energy of a single photon.…”
Section: Chasing Safe Exposure To Light Sourcesmentioning
confidence: 99%
“…This is because NIR light (700-1700 nm) shows deeper tissue-penetration than visible light and reduced photodamage to cells and tissues. [10][11][12] The targeted photodynamic therapy and photothermal therapy by NIR were studied to release drugs and overcome the barriers on demand. [12][13][14] Graphene oxide (GO) nanosheets have strong and broad absorption on NIR and could effectively convert NIR light energy to heat, which make it an ideal material to disrupt barriers by thermal effect.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] The targeted photodynamic therapy and photothermal therapy by NIR were studied to release drugs and overcome the barriers on demand. [12][13][14] Graphene oxide (GO) nanosheets have strong and broad absorption on NIR and could effectively convert NIR light energy to heat, which make it an ideal material to disrupt barriers by thermal effect. [15][16][17][18][19][20] Therefore, the study of the targeted and NIR-irradiative photothermal effect of GO and its effect on the cellular barrier disruption is necessary.…”
Section: Introductionmentioning
confidence: 99%